2017
DOI: 10.3389/fimmu.2017.01228
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Role of Neuropilins in the Immune System: Potential Targets for Immunotherapy

Abstract: Neuropilins (NRPs) are non-tyrosine kinase cell surface glycoproteins expressed in all vertebrates and widely conserved across species. The two isoforms, such as neuropilin-1 (NRP1) and neuropilin-2 (NRP2), mainly act as coreceptors for class III Semaphorins and for members of the vascular endothelial growth factor family of molecules and are widely known for their role in a wide array of physiological processes, such as cardiovascular, neuronal development and patterning, angiogenesis, lymphangiogenesis, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
227
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(237 citation statements)
references
References 281 publications
(226 reference statements)
3
227
2
5
Order By: Relevance
“…NRP1 is expressed in a wide range of non‐tumor cells that may be present in a tumor, including endothelial cells, fibroblasts, and bone marrow‐derived macrophages and immune cells ; moreover, tumor cells may also express NRP1 . The potential prognostic effect of NRP1 expression in cancer has, however, remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…NRP1 is expressed in a wide range of non‐tumor cells that may be present in a tumor, including endothelial cells, fibroblasts, and bone marrow‐derived macrophages and immune cells ; moreover, tumor cells may also express NRP1 . The potential prognostic effect of NRP1 expression in cancer has, however, remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Since SEMA3s compete with VEGF for NRP binding, treatment with SEMA3s may enhance anti-tumor activity by impairing Treg infiltration induced by VEGF. However, the functions of NRP2 in immune systems are poorly understood ( Roy et al, 2017 ; Schellenburg et al, 2017 ). Further studies are needed to identify the effect of SEMA3F as an immune modulator.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that aberrant expression of axonal guidance cue molecules such as semaphorins in cancer, and their dysregulated signaling plays a significant role in cancer angiogenesis and metastasis [ 4 9 ]. Several studies have demonstrated the expression and role of subclass-5 member Semaphorin-5A (SEMA5A) in various malignancies including glioma, lung, prostate, pancreas, melanoma and gastric [ 10 – 23 ]. SEMA5A has not been associated with a univocal role in cancer [ 17 ], as it acts as a tumor promoter in cancers like gastric [ 14 16 ], prostate [ 20 ] and, ovary [ 23 ] while it acts as a tumor suppressor in glioma [ 11 , 12 ] and lung cancer [ 13 ].…”
Section: Introductionmentioning
confidence: 99%